Entering the Stream to Enlightenment: Experiences of the Stages of the Buddhist Path in Contemporary Sri Lanka, by Yuki Sirimane. - Kyaw, Pyi Phyo (Buddhist Studies Review, 2018)
Entering the Stream to Enlightenment: Experiences of the Stages of the Buddhist Path in Contemporary Sri Lanka, by Yuki Sirimane. Equinox Publishing, 2016. 366pp. Hb. £75.00, ISBN-13: 9781781792032; Pb. £24.99, ISBN-13: 9781781792049.